KINERJA KEUANGAN DAERAH PADA ERA OTONOMI DAERAH (Suatu Kajian Empiris di propinsi Jawa Timur) - TriPitono Adi Prabowo (MediaTrend, 2006)
The objectives of this study were to empirically compare and analyze the financial performance of municipal/city goverment before and after the autonomy policy. using three measurements for financial performance-expenditure capability, mobility and fiscal decentralization -this study perform the comparison due to "the autonomy policy" in the economic condition of fiscal stress (economic crisis). The hypothesis were tested using paired sample t test and wilcoxon match pairs test. The result show that genarally there are no diffrent of the municipal/city government financial performance before and after the autonomy policy, except for the financial decentralization.